Evaluating World Religion Paradigm through the Idea of Ultimate Reality - Andi Alfian (Islam Transformatif : Journal of Islamic Studies, 2022)
This study aims to evaluate whether the idea of ultimate reality in world religions contributes to the characteristics of the world religion paradigm, which is hierarchical cosmology or “subject-object cosmology.” Several research on this topic claims that one of the characteristics of the world religion paradigm is its hierarchical perspective. Discussing this issue is important to distinguish the world religions as the paradigm and the world religions as the most widely embraced religion. This study argues that the hierarchical perspective of the world religion paradigm can be rooted in the idea of ultimate reality, that there is a supreme, foremost, and most principal reality in the continuity of this universe, namely the supernatural or God. The hierarchical cosmology consists of three main domains: supernatural/God, culture/human, and nature. This study uses a literature study methodology, relying on books, journals, and texts related to research questions. This study finds that the world religion paradigm or hierarchical cosmology or “subject-object cosmology” is prominent, especially in Abrahamic religions such as Islam, Christianity, and Judaism, even though the concept of ultimate reality in these three religions is different. Penelitian ini bertujuan untuk mengevaluasi apakah gagasan tentang realitas tertinggi dalam agama-agama dunia turut berkontribusi membentuk karakteristik paradigma agama dunia, yaitu kosmologi hierarkis atau “kosmologi subjek-objek”. Beberapa penelitian tentang topik ini mengklaim bahwa salah satu karakteristik paradigma agama dunia adalah perspektifnya yang hierarkis. Membahas masalah ini penting untuk membedakan agama-agama dunia sebagai paradigma dan agama-agama dunia sebagai agama yang paling banyak dianut. Kajian ini berpendapat bahwa perspektif hierarkis paradigma agama dunia dapat berakar pada gagasan tentang realitas tertinggi, bahwa ada realitas tertinggi, utama, dan paling utama dalam kelangsungan alam semesta ini, yaitu supernatural atau Tuhan. Kosmologi hierarkis terdiri dari tiga domain utama: supernatural/Tuhan, budaya/manusia, dan alam. Penelitian ini menggunakan metodologi studi kepustakaan, dengan mengandalkan buku, jurnal, dan teks-teks yang berkaitan dengan pertanyaan-pertanyaan penelitian. Kajian ini menemukan bahwa paradigma agama dunia atau kosmologi hierarkis atau “kosmologi subjek-objek” menonjol, terutama dalam agama-agama Abrahamik seperti Islam, Kristen, dan Yudaisme, meskipun konsep realitas tertinggi dalam ketiga agama tersebut berbeda.